2021
DOI: 10.1051/0004-6361/202039229
|View full text |Cite
|
Sign up to set email alerts
|

Multi-thermal atmosphere of a mini-solar flare during magnetic reconnection observed with IRIS

Abstract: Context. The Interface Region Imaging Spectrograph (IRIS) with its high spatial and temporal resolution facilitates exceptional plasma diagnostics of solar chromospheric and coronal activity during magnetic reconnection. Aims. The aim of this work is to study the fine structure and dynamics of the plasma at a jet base forming a mini-flare between two emerging magnetic fluxes (EMFs) observed with IRIS and the Solar Dynamics Observatory instruments. Methods. We proceed to a spatio-temporal analysis of IRIS spect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 78 publications
1
27
0
Order By: Relevance
“…In this paper we extend the IRIS data analysis of the mini flare studied in Joshi et al (2020Joshi et al ( , 2021 and present the Balmer continuum around 2832 Å observed with IRIS (Sect. 2).…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations
“…In this paper we extend the IRIS data analysis of the mini flare studied in Joshi et al (2020Joshi et al ( , 2021 and present the Balmer continuum around 2832 Å observed with IRIS (Sect. 2).…”
Section: Introductionmentioning
confidence: 94%
“…In the 2832 continuum filter, small bright dots are observed at the location of the mini flare (green and blue boxes). For an accurate comparison between the AIA images and IRIS SJIs, we manually aligned these images by shifting the IRIS SJIs by 4 in x-axis and 3 in y-axis, as noted in the previous paper (Joshi et al 2021). The relation between heliographic coordinates and pixels along the slit of the spectra is shown in Fig.…”
Section: Aia and Iris Sjimentioning
confidence: 99%
See 2 more Smart Citations
“…An understanding of the physics of microflares remains elusive, as key spatially-resolved spectroscopic observations have been lacking, and given that they have peak temperatures in the 4-8 MK range (see e.g., Feldman et al, 1996;Hannah et al, 2019;Mitra-Kraev and Del Zanna, 2019;Cooper et al, 2020;Vadawale et al, 2021 1 ) which have largely been unexplored by previous and current imaging spectrometers. Consequently, only a few models of microflare loops and associated events have been developed (see e.g., Testa and Reale, 2020;Joshi et al, 2021). Some information has been provided with imaging spectroscopy of Bremsstrahlung emission with e.g., NuSTAR and FOXSI-2.…”
Section: From Flares To Microflaresmentioning
confidence: 99%